Popular culture and public imaginary - Yin, Jing (Javnost (Ljubljana), 2011)
This case study is an attempt to challenge the dominant narrative of a U.S. popular cultural text that has shaped the public imaginary of a non-Western culture and to open up the possibility of re-constructing alternative narratives, imaginaries, cultural spaces, and identities. More specifically, the present analysis investigates the process that Disney appropriated the Chinese legend of Mulan into a "universal" classic and offers an interpretation of The Ballad of Mulan, upon which the Disney film was based, as a form of counter-rhetoric for negotiating the dominant image produced by Disney. This case study demonstrates that Disneyćs appropriation simultaneously reinforced the existing racial and gender ideologies through deprecating Chinese culture as an Oriental despotism and dissolving feminism into the cultural/racial hierarchy. Contrary to the overriding theme of individualism in the Disney version, the original Ballad reflects the Chinese ethos of relationalism, filial piety, and loyalty and embraces an alternative form of feminism that is predicated on the Chinese preference for the collective.
Keywords: množična kultura; množično komuniciranje; popularna kultura